ChemInform Abstract: Stereoselective β‐C‐Glycosylation by a Palladium‐Catalyzed Decarboxylative Allylation: Formal Synthesis of Aspergillide A. Issue 40 (12th September 2013) - Zeng, Jing; Ma, Jimei; Xiang, Shaohua; Cai, Shuting; Liu, Xue‐Wei
Abstract The process allows a convenient synthesis of glycals of type (II), (IV), and (VI).